Rekonstruksi Norma Perlindungan Pembeli Lelang Eksekusi Hak Tanggungan Berbasis Nilai Keadilan dalam Rangka Pembaruan Hukum Jaminan Nasional - Rusdan Arifin Al Mugni; Nazwa Putri Senjaya; Tiara Ananda; Ghozi Fausan Purnama (Jurnal Hukum Lex Generalis, 2026)
This study examines the weaknesses of the regulatory framework governing the protection of auction buyers in mortgage executions, which remains insufficiently grounded in substantive justice and proposes a normative reconstruction within the framework of national security law reform. Using normative legal research with statutory, conceptual and case approaches, it finds that regulatory disharmony, ambiguous legal status of auction minutes and ineffective eviction mechanisms place bona fide purchasers in a structurally vulnerable position. The reconstruction proposed strengthens the executorial force of auction minutes, clarifies creditor liability, refines reserve price rules, institutionalises pre-auction mediation, introduces layered compensation schemes and codifies these protections in a justice-oriented National Auction Act.